ROTATIONAL TEMPERATURES OF THE AURORAL 3914 ANGSTROM NITROGEN BAND VS. HEIGHT AT CHURCHILL, MANITOBA - Brandy,J. H. (1964)
Rotational temperatures derived from spectrometric scans of the 3914 Angstrom N2(+) band in the aurora have been made over a height range from 93 to 160 km. Simultaneous measurements of heights of lower borders were made using parallactic photography. The temperature range of approximately 190 to 570 K agrees well with Hunten's profile and tends to confirm the gradient between 110 and 160 km at 5.2 degree/km. (Author)